2023
DOI: 10.3390/nu15245136
|View full text |Cite
|
Sign up to set email alerts
|

Combined Exercise Training and Nutritional Interventions or Pharmacological Treatments to Improve Exercise Capacity and Body Composition in Chronic Obstructive Pulmonary Disease: A Narrative Review

Bente Brauwers,
Felipe V. C. Machado,
Rosanne J. H. C. G. Beijers
et al.

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease that is associated with significant morbidity, mortality, and healthcare costs. The burden of respiratory symptoms and airflow limitation can translate to reduced physical activity, in turn contributing to poor exercise capacity, muscle dysfunction, and body composition abnormalities. These extrapulmonary features of the disease are targeted during pulmonary rehabilitation, which provides patients with tailored therapies to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 272 publications
0
1
0
Order By: Relevance
“…Thus, it is necessary to consider adding interventions to correct energy imbalance in patients who lose body weight during pulmonary rehabilitation with high-intensity exercise. Several studies have shown the positive effects of nutritional supplements on increasing energy intake during pulmonary rehabilitation in patients with COPD [8]. However, no studies have focused on reducing energy expenditure by adjusting exercise intensity (i.e., mitigating exercise intensity) during pulmonary rehabilitation to regulate energy imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to consider adding interventions to correct energy imbalance in patients who lose body weight during pulmonary rehabilitation with high-intensity exercise. Several studies have shown the positive effects of nutritional supplements on increasing energy intake during pulmonary rehabilitation in patients with COPD [8]. However, no studies have focused on reducing energy expenditure by adjusting exercise intensity (i.e., mitigating exercise intensity) during pulmonary rehabilitation to regulate energy imbalance.…”
Section: Introductionmentioning
confidence: 99%